Analyzing Factor that Affecting of Ventilator Associated Pneumonia - Yuliyana Kumaladewi; Sari Fatimah; Aan Nuraeni (Jurnal Keperawatan Padjadjaran, 2018)
AbstractBackground: Ventilator associated pneumonia (VAP) has been known to be the most common nosocomial infection in Intensive Care Unit (ICU). VAP increases length of care, cost, morbidity and mortality of patients in ICU. The ICU of RSMH Palembang have already been doing prevention of VAP incidence through VAP bundles, but the number of incidence were still high. Purpose: This study aimed to identify the factors associated with VAP incidence among the patients in ICU RSMH Palembang. Method: this study was quantitative study with kohort prospective approach. Samples were recruited from ICU RSMH Palembang using consecutive sampling technique for 4 months period (n=61). Data were collected using a questionnaire package consisting of a demographic questionnaire, CPIS instrument, APACHE II, an observation sheets that measure duration of using antibiotics, duration of using ventilator, reintubation and hand hygiene compliance. Data were analyzed using descriptive quantitative and logistic regression analysis. Results: VAP occured in 12 patients (19.7%). Bivariate test result with α:5% have shown that APACHE II (p:0.043), duration of using antibiotic (p:0.023), duration of using ventilator (p:0.001) and reintubation p:(0.001) were related to the incidence of VAP. Logistic regression analysis shows that reintubation (OR=0.035; CI 95%:0.28-0.658; p=0.013) and duration of ventilator > 5 days (OR=0.082; CI 95%: 0.09-0.74; p=0.026) were significant factor that affecting VAP. Conclusion. Reintubation was the most related factor with VAP incidence. It is recommended for doctors and nurses to conduct a proper and thorough assessment before extubation to minimalize the risk of reintubation.